Density functional study of hydrogen adsorption and diffusion on Ni‐loaded graphene and graphene oxide. Issue 13 (15th April 2014) - Li, Qingzheng; Wang, Houyuan; Xia, Haiping; Wei, Shihao; Yang, Jianhui
<x xml:space="preserve">Abstract</x> In this work, we performed density functional calculations to investigate the adsorption and diffusion of hydrogen on Ni‐loaded graphene and single layer graphene oxide (SLGO). We evaluated the feasibility of hydrogen spillover in the presence of Ni4 cluster and the role of oxygen‐containing groups. Our calculations indicate that the hydrogen diffusion is difficult to take place on the Ni/graphene interface due to the stronger NiH bond strength. Further, the chemisorbed H atoms are also hard to diffuse freely on the graphene surface. For the SLGO surface, both hydroxyl and epoxide groups may not facilitate the hydrogen diffusion. Instead, they are readily attracted by the nearby Ni catalyst and hydrogenated to water molecules. © 2014 Wiley Periodicals, Inc.